1999
DOI: 10.2307/2641332
|View full text |Cite
|
Sign up to set email alerts
|

Bias, Precision, and Accuracy of Four Measures of Species Richness

Abstract: Species richness is a widely used surrogate for the more complex concept of biological diversity. Because species richness is often central to ecological study and the establishment of conservation priorities, the biases and merits of richness measurements demand evaluation. The jackknife and bootstrap estimators can be used to compensate for the underestimation associated with simple richness estimation (or the sum of species counted in a sample). Using data from five forest communities, we analyzed the simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
2
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(130 citation statements)
references
References 15 publications
6
117
2
5
Order By: Relevance
“…An approach more comparable to ours was used by Hellmann and Fowler (1999), who recorded the presence of all species in five 0.4 ha plots divided into a series of smaller (5 × 5 m) quadrats within which species presence/absence was recorded. These subplots were then sampled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An approach more comparable to ours was used by Hellmann and Fowler (1999), who recorded the presence of all species in five 0.4 ha plots divided into a series of smaller (5 × 5 m) quadrats within which species presence/absence was recorded. These subplots were then sampled.…”
Section: Discussionmentioning
confidence: 99%
“…MRE is equivalent to the 'mean deviation' of Palmer (1990) and to the 'bias' of Hellmann and Fowler (1999), except that it is scaled by the true value, being equivalent to the 'bias' used by Walther and Morand (1998). MSRE is equivalent to the 'mean square proportional deviation' of Palmer (1990) and the 'deviation' of Walther and Morand (1998).…”
Section: Comparison Of Estimators' Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The performance of various species richness estimators has been tested using field or simulated datasets with the study taxon being either animal or plant communities; see Table 3 in Walther and Moore (2005) for a list. Our motivation comes from the test results regarding plant communities in Gimaret-Carpentier et al (1998);Hellmann and Fowler (1999); and Chiarucci et al (2003). Based on their investigations, no estimator provides reasonable estimates when the sample proportion is small.…”
Section: Introductionmentioning
confidence: 99%
“…H&F's estimator is described as a jackknife and S&vB's as a bootstrap estimator. The performance of these estimators was compared in five real populations by Hellman and Fowler (1999), who found that none is best for all sample sizes and population types. The M&M and Mingoti estimators are based on models for how the individuals of each species are distributed among the quadrats, and the estimation uses empirical Bayes and Bayes methodology, respectively.…”
Section: Introductionmentioning
confidence: 99%